2021
DOI: 10.1002/jmv.27319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of demographic and clinical characteristics of hospitalized COVID‐19 patients with severe/critical illness in the first wave versus the second wave

Abstract: Due to current advances and growing experience in the management of coronavirus Disease 2019 , the outcome of COVID-19 patients with severe/critical illness would be expected to be better in the second wave compared with the first wave. As our hospitalization criteria changed in the second wave, we aimed to investigate whether a favorable outcome occurred in hospitalized COVID-19 patients with only severe/critical illness. Among 642 laboratory-confirmed hospitalized COVID-19 patients in the first wave and 1121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
(43 reference statements)
6
14
1
Order By: Relevance
“…Among the non-vaccinated patients in our study, main baseline characteristics were in accordance with studies from previous COVID-19 waves [ 12 , 29 32 ]. Hospitalized vaccinated patients were older, predominantly males and had more comorbidities.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Among the non-vaccinated patients in our study, main baseline characteristics were in accordance with studies from previous COVID-19 waves [ 12 , 29 32 ]. Hospitalized vaccinated patients were older, predominantly males and had more comorbidities.…”
Section: Discussionsupporting
confidence: 84%
“…It is possible that because of their baseline characteristics, vaccinated patients had higher likelihood of comorbidity-related complications secondary to COVID-19 and were less reluctant to arrive to the hospital. The general mean hospital duration was 8 days, which is shorter than several previous cohorts (10–13 days) [ 11 , 32 , 33 ]. Only severe patients were included in our cohort, further highlighting the gap in hospital duration from previous studies.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This variation in outcomes over time could be attributed to the emergence of new variants/mutants of the virus, improvement in overall understanding of the disease management such as evolving therapeutic regimes, preparedness in healthcare settings, and most importantly, the implementation of mass vaccination drives. Our observations are consistent with other studies that reported both similarities [ 24 ] and variations [ 21 ] in their data over a period of time. All the above observations are presented in Supplementary Tables 1 - 4 .…”
Section: Discussionsupporting
confidence: 93%
“…The period of the patients’ inclusion in the study was long, covering both the first and second wave of the pandemic disease. This might have affected the demographic and clinical characteristics of patients admitted to the hospital, and the choice of treatment, adequately to the changing knowledge about the specific course of COVID-19, and finally the mortality rate [ 54 ]. On the other hand, the study covered a large group of patients, analyzing not only in-hospital mortality, but also deaths within 90 and 180 days from admission to hospital, which may increase the strength of the obtained results.…”
Section: Discussionmentioning
confidence: 99%